PENGARUH MASSA KARBON AKTIF DAN KONSENTRASI ADSORBAT DALAM PENYERAPAN ZAT WARNA METILEN BLUE - Dennis Nury; Muhammad Zulfikar Luthfi; Deviany Deviany; Feerzet Achmad; Jabosar Ronggur Hamonangan Panjaitan (Institut Sains dan Teknologi Al-Kamal, 2023)
In this study, the effect of activated carbon mass and methylene blue solution concentration on adsorption capacity, the length of time required to reach equilibrium, and isothermal modeling of activated carbon material in the adsorption process were studied. The variables used are the mass of activated carbon as much as 100 mg, 75 mg, and 50 mg and the concentration of methylene blue solution of 20, 40, 60, 80, and 100 ppm. The adsorption process in the three mass variations occurred at an optimum contact time of 80 and 90 minutes with an adsorption percentage of 99%. Adsorption of methylene blue dye by activated carbon from durian peel follows Freundlich isothermal modeling with a K value of 15846.44 mg/g and 1/n of 23.666 which shows an indicator of concentration dependence of the amount of energy associated with the adsorption process.